A Methodology for Fast and Accurate Analytical Fragility Analysis of Linear Structural Systems during Wind Storms: ALFA - Ciftci, Cihan (My University, 2023)
Wind-storms are extremely destructive natural disasters that cause structural damage, and consequently severe personal injuries and casualties. To reduce these injuries and casualties, risk assessment of existing structures and improvement of building design regulations have become important. To assess the risk of structural systems during wind storms, analytical fragility analysis is a recently developed method by providing conditional failure probabilities for the structural systems. However, the analytical fragility analysis requires extensive computational time and effort which makes it infeasible for large scale structures. This proposed paper develops a new methodology (Analytical Linear Fragility Analysis: ALFA) to simplify and to expedite the analytical fragility analysis for linear structural systems without compromising accuracy. ALFA is exemplified by obtaining the fragility curves of 70 different multi-degree of freedom (MDOF) linear mass-column systems subjected to varying wind loading conditions. The fragility curves of the same mass-column systems were also obtained using Monte-Carlo (MC) based brute-force methodology, which is a commonly used computationally expensive method in literature, and results are compared. This comparison yields the conclusion that ALFA is 240 times faster than the brute-force one, without losing accuracy. Moreover, ALFA can be utilized for improvement of performance-based design specifications and for the preliminary risk assessment of nonlinear structural systems.

Rüzgar fırtınaları, yapısal hasara ve sonuç olarak ciddi kişisel yaralanmalara ve kayıplara neden olan son derece yıkıcı doğal afetlerdir. Bu yaralanma ve can kayıplarını azaltmak için mevcut yapıların risk değerlendirmesi ve bina tasarım yönetmeliklerinin iyileştirilmesi önem kazanmıştır. Rüzgar fırtınaları sırasında yapısal sistemlerin riskini değerlendirmek için, analitik kırılganlık analizi, yapısal sistemler için koşullu arıza olasılıkları sağlayarak son zamanlarda geliştirilen bir yöntemdir. Bununla birlikte, analitik kırılganlık analizi, büyük ölçekli yapılar için uygulanamaz hale getiren kapsamlı hesaplama zamanı ve çabası gerektirir. Önerilen bu makale, doğruluktan ödün vermeden doğrusal yapısal sistemler için analitik kırılganlık analizini basitleştirmek ve hızlandırmak için yeni bir metodoloji (Analitik Lineer Kırılganlık Analizi: ALFA) geliştirmektedir. ALFA, değişen rüzgar yükü koşullarına maruz kalan 70 farklı çok serbestlik dereceli (MDOF) lineer kütle kolon sisteminin kırılganlık eğrilerinin elde edilmesiyle örneklenmiştir. Literatürde hesaplama açısından pahalı bir yöntem olan Monte-Carlo (MC) tabanlı kaba kuvvet metodolojisi kullanılarak aynı kütle-kolon sistemlerinin kırılganlık eğrileri de elde edilmiş ve sonuçlar karşılaştırılmıştır. Bu karşılaştırma, ALFA'nın kesinliği kaybetmeden kaba kuvvetten 240 kat daha hızlı olduğu sonucunu verir. Ayrıca ALFA, performansa dayalı tasarım özelliklerinin iyileştirilmesi ve doğrusal olmayan yapısal sistemlerin ön risk değerlendirmesi için kullanılabilir.
Rüzgar Fırtınaları sırasında Lineer Yapısal Sistemlerin Hızlı ve Doğru Analitik Kırılganlık Analizi için bir Metodoloji: ALFA
Keywords: İnşaat Mühendisliği; Mühendislik, Makine